Analisis Empiris Transformasi Digital UMKM Pasca-Pandemi terhadap Kinerja Keuangan Berbasis Model Technology Acceptance di Indonesia - Syamsul Bahri; Arif Kurnianto; Darmawati Darmawati (JURNAL ECONETICA: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
This study aims to empirically analyze the influence of digital transformation on the financial performance of MSMEs in Indonesia in the post-pandemic period using the Technology Acceptance Model approach as a mediating variable. This study employed a quantitative method with a survey approach of MSMEs that have adopted digital technology in their business operations. The data analysis technique used Structural Equation Modeling based on Partial Least Squares to simultaneously test the relationship between variables. The results showed that digital transformation has a positive and significant influence on the financial performance of MSMEs. The adoption of digital technology has been shown to improve operational efficiency, expand market access, and drive business revenue growth. In addition, perceived ease of use and perceived usefulness as the main constructs in the Technology Acceptance Model have been shown to significantly influence the intention to use technology by MSMEs. This study also found that the Technology Acceptance Model acts as a mediating variable in the relationship between digital transformation and financial performance. This indicates that the success of digital transformation is highly dependent on the level of acceptance and utilization of technology by users. These findings confirm that behavioral factors play a critical role in determining the effectiveness of technology implementation in improving business performance. This research provides theoretical contributions to the development of digital transformation and MSME studies, as well as practical implications for business actors and policy makers in encouraging more optimal technology adoption.